Dopaminergic and serotonergic modulation of anterior insular and orbitofrontal cortex function in risky decision making. (March 2015) - Ishii, Hironori; Ohara, Shinya; Tobler, Philippe N.; Tsutsui, Ken-Ichiro; Iijima, Toshio
Highlights: We investigated DA and 5-HT modulation of AIC and OFC function in risky choice. Blocking 5-HT1A R in OFC decreased risk preference. AIC D2 R and 5-HT1A R had different outcome history-dependent effects on risky choice. Blocking D2 R in AIC increased risk preference particularly after winning gambles. Blocking 5-HT1A R in AIC increased risk preference particularly after losing gambles. Abstract: Systemic manipulations have shown that dopamine and serotonin systems are involved in risky decision making. However, how they work within the regions that implement risky choices remains unclear. The present study investigated the role of dopamine and serotonin in the rat anterior insular cortex (AIC) and orbitofrontal cortex (OFC), which make different contributions to risky decision making. We examined the effects of local injection of the D1 (SCH23390), D2 (eticlopride), 5-HT1A (WAY100635) and 5-HT2A (M100907) receptor antagonists into the AIC or OFC on risk preference in a gambling task. We found that different dopamine and serotonin receptor subtypes in the AIC and OFC differentially influence risky decision making: intra-AIC injection of D2 R or 5-HT1A R blockers increased risk preference whereas intra-OFC injection of the 5-HT1A R blocker decreased it. Risk preference was not altered by intra-AIC injection of D1 R and 5-HT2A R blockers or by intra-OFC injection of D1 R, D2 R, and 5-HT2A R blockers. Furthermore, additional analyses revealed that dopamine and serotonin signaling in the AIC have outcome history-dependent effects on risk taking: intra-AIC injection of the D2 R blocker increased risk preference particularly after winning in a previous risky choice, whereas intra-AIC injection of the 5-HT1A R blocker increased risk preference after losing.